Asuhan Keperawatan pada Tn. N dengan Gangguan Sistem Endokrin : Diabetes Melitus di Ruang Dahlia RSUD dr. Soeselo Kabupaten Tegal - Meita Eni Peniar; Tati Karyawati; Muhammad Silahudin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The endocrine system is a ductless body control system that produces hormones to regulate various organs and physiological processes. Hormones act as important biological messengers in the human body. One of the most essential hormones is insulin, which plays a key role in blood sugar regulation. Insufficient insulin production or impaired insulin action can cause disruption of blood glucose control, leading to diabetes mellitus. Diabetes mellitus is a chronic metabolic disorder characterized by persistently high blood glucose levels caused by impaired insulin secretion, insulin action, or both. The purpose of this paper is to apply nursing care to Mr. N, a patient with endocrine system disorders: diabetes mellitus, treated in the Dahlia Ward of Dr. Soeselo Regional Hospital, Tegal Regency. This descriptive case study method was used to explain the nursing process in a structured manner. The main complaint presented by the client was pain in the wound on the left foot. Four nursing diagnoses were identified during the assessment, namely unstable blood glucose levels, acute pain, impaired skin/tissue integrity, and knowledge deficit. Nursing interventions were developed and implemented based on the Standar Diagnosis Keperawatan Indonesia (SDKI), Standar Luaran Keperawatan Indonesia (SLKI), and Standar Intervensi Keperawatan Indonesia (SIKI). The case highlights the importance of comprehensive nursing care in diabetes management, with a focus on blood glucose stabilization, pain management, wound care, and patient education. The results of this study are expected to provide additional references for clinical practice and strengthen the role of nurses in preventing complications of diabetes mellitus.